"Dicranin" in the Membrane Phospholipids of a Dicranaceae and Pottiaceae Moss Member of the Eastern Himalayan Biodiversity Hotspot. Issue 5 (2nd August 2018) - Roy Chowdhuri, Sumedha; Biswas Raha, Anashuya; Mitra, Souvik; Datta, Jayashree; Poddar Sarkar, Mousumi
Abstract: The phospholipids of two moss samples Oreoweisia laxifolia (Hookf.) Kindb. (family‐Dicranaceae Schimp.) and Leptodontium viticulosoides (P. Beauv.) Wijk & Margad (family‐Pottiaceae Schimp.) of the Eastern Himalayan Biodiversity Hotspot were investigated to find out any peculiarity in their fatty acid profiles. Detailed analysis of phospholipid classes and the respective fatty acids was performed using high‐performance thin‐layer chromatography and gas chromatography‐mass spectrometry. An array of different saturated and unsaturated fatty acids were detected in both the samples. Although it has been proposed previously that acetylenic fatty acids are associated only with triacylglycerol of storage lipids, the most striking observation of the present investigation is the abundance of an acetylenic fatty acid, octadeca‐6‐yn‐9, 12, 15‐trienoic acid (18:4a), or Dicranin, in the phospholipids of both the mosses. The position of the triple bond in the hydrocarbon chain of the fatty acids was confirmed by dimethyloxazoline derivatization of fatty acids and their characteristic mass fragmentation pattern. The occurrence of Dicranin in phospholipids and in the Pottiaceae family is reported for the first time, with substantial explanations of the observed results. This may raise the issue of rethinking "Dicranin" as a chemotaxonomic marker of Dicranaceae.